PENGARUH SOSIALISASI PERPAJAKAN TERHADAP KETAATAN WAJIB PAJAK MEMBAYAR PAJAK DI KOTA BANDA ACEH - Rahmah Yulianti (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2015)
The purpose of this research is to study the effect of taxation on the observance of socialization taxpayers pay taxes. This study used a questionnaire as an instrument to collect data. Questionnaires were distributed to the community in Banda Aceh which is the taxpayer, which consisted of 100 respondents. Data were analyzed using to evaluate the validity and reliability of the questionnaire and use linear regression to evaluate the factors that influence of variable. The data were analyzed using the SPSS program to test whether the mode l used in this study appropriates as the model analyzed.T he result shows that awareness of paying taxes significantly influence adherence to pay taxes, It can be seen from the independent variable coefficient value of 0264 while the variable knowledge and understanding of the rules of taxation that has a value of coefficient of 0448. This suggests that the taxpayer in the city of Banda Aceh obedient to pay taxes if there is dissemination of knowledge and understanding of the rules of taxation, compared with consideration of awareness to pay taxes.